A conceptual integrated persuasive behavioral change framework based on Maqasid al-Shariah to encourage green practices of Municipal Solid Waste (MSW) disposal - Shompa, Zohora Azmin; Mohd Mohadis, Hazwani (Faculty Information & Science Technology, International Islamic University College Selangor (KUIS), 2022)
Waste disposal has been a worldwide concern for several decades and the situation is worsening in developing countries including Malaysia due to the progressive increase in waste generation in recent years. Improper waste disposal causes a detrimental effect on the environment and human health. In many developing countries, environmentally friendly practices (reduce, reuse and recycle) have been introduced to reduce the amount of waste generated and alternative methods of final waste disposal are increasingly used to reduce environmental impact. However, most Malaysians have weak awareness of such green practices of MSW disposal despite numerous efforts made by the government. Therefore, how to motivate Malaysians to adopt green practices has been of concern. Within sustainable HCI, persuasive technology has been used to intentionally change user’s behaviors and attitudes through persuasion. However, one of the major limitations of persuasive technologies is, it does not consider how one’s culture and religious views shapes their behavior. As Malaysia is a Muslim-majority country and largely influenced by religious views in guiding and making a positive change in their attitudes and behaviors, we believed integrating persuasive technology with Maqasid al-Shariah would enhance its persuasive power at encouraging green practices of solid waste disposal. Accordingly, in this paper we are proposing a conceptual integrated persuasive behavioral change framework based on Maqasid al- Shariah aiming to encourage green practices of MSW disposal among Malaysians. We hypothesized this framework will be beneficial to increase Malaysian community awareness on the importance of disposing MSW based on Maqasid al-Shariah and eventually reduce risks to health and the environment due to improper waste disposal.